2010
DOI: 10.3389/fnint.2010.00127
|View full text |Cite
|
Sign up to set email alerts
|

“Stay Tuned”: Inter-Individual Neural Synchronization During Mutual Gaze and Joint Attention

Abstract: Eye contact provides a communicative link between humans, prompting joint attention. As spontaneous brain activity might have an important role in the coordination of neuronal processing within the brain, their inter-subject synchronization might occur during eye contact. To test this, we conducted simultaneous functional MRI in pairs of adults. Eye contact was maintained at baseline while the subjects engaged in real-time gaze exchange in a joint attention task. Averted gaze activated the bilateral occipital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
163
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(184 citation statements)
references
References 72 publications
10
163
2
Order By: Relevance
“…Corroborating previous findings of studies investigating JA and social cognition (25,38), we initially demonstrated that self-initiated JA vs. NJA recruited several reward-related areas (mPFC, mOFC, and PCC) in our control participants. These areas have repeatedly been shown to be associated with social cognition (39).…”
Section: Discussionsupporting
confidence: 82%
“…Corroborating previous findings of studies investigating JA and social cognition (25,38), we initially demonstrated that self-initiated JA vs. NJA recruited several reward-related areas (mPFC, mOFC, and PCC) in our control participants. These areas have repeatedly been shown to be associated with social cognition (39).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, both an activation in part of the fronto-parietal control network and a deactivation in the default mode network have been observed when participants were imitated, compared with when they imitated others (Guionnet et al, 2012). However, there are only a handful of studies that explore neural mechanisms of social interaction in an interactive context (Guionnet et al, 2012;Redcay et al, 2010;Saito et al, 2010;Schilbach et al, 2010;Tognoli et al, 2007), though social interaction is a coregulated coupling activity that involves at least two autonomous agents. As Guionnet et al has pointed out, the major reason for this paucity may be attributed to the methodological and technical difficulties associated with creating a natural social interaction within an MRI environment.…”
Section: Issues For Future Studiesmentioning
confidence: 99%
“…One group of such studies has employed pseudo-interactive scenarios, scanning one person at a time in unidirectional interactions (Schippers et al, 2010, Stephens et al, 2010, Anders et al, 2011, Kuhlen et al, 2012, while others have measured two-brain processes during either turn-based or continuous, mutual interactions, employing fMRI (e.g. Montague et al, 2002, KingCasas et al, 2005, Saito et al, 2010, EEG (e.g. Lindenberger et al, 2009, Dumas et al, 2010, Dodel et al, 2011, Yun et al, 2012, or fNIRS (e.g.…”
Section: Introductionmentioning
confidence: 99%